Organizational Culture, Job Satisfaction, and Work Motivation on Employee Performance: Literature Review - Wardani, Mariani Ika; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Organizational culture becomes important in competing if the culture can support organizational strategy, is able to answer and overcome competitive challenges and changes that occur appropriately and responsively. If someone is motivated, he will try to do his best to realize what he wants. Employee job satisfaction is basically very individualistic depending on the personality of each employee.The research aims to review the results of research on organizational culture, job satisfaction, and work motivation on employee performance. The literature review method is based on reference sources and research results with a synthesis matrix technique used in the analysis process. Journal reviews were obtained by searching Science Direct and Google Scholar. A total of 25 journals were reviewed based on theory, research on organizational culture, job satisfaction, and work motivation on employee performance. The results of the review show that organizational culture, job satisfaction, and employee motivation are aspects that can affect employee performance.